2018
DOI: 10.3389/fnins.2018.00715
|View full text |Cite
|
Sign up to set email alerts
|

Does Impedance Matter When Recording Spikes With Polytrodes?

Abstract: Extracellular microelectrodes have been widely used to measure brain activity, yet there are still basic questions about the requirements for a good extracellular microelectrode. One common source of confusion is how much an electrode’s impedance affects the amplitude of extracellular spikes and background noise. Here we quantify the effect of an electrode’s impedance on data quality in extracellular recordings, which is crucial for both the detection of spikes and their assignment to the correct neurons. This… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 43 publications
2
86
0
Order By: Relevance
“…1). The impedance magnitude and phase of the recording electrodes were measured as 1.15 ± 0.07 MΩ and -68.33 ± 5.11°at 1 kHz (n = 54, mean ± SD), respectively, acceptable for high-quality in vivo extracellular recordings 32 .…”
Section: Resultsmentioning
confidence: 99%
“…1). The impedance magnitude and phase of the recording electrodes were measured as 1.15 ± 0.07 MΩ and -68.33 ± 5.11°at 1 kHz (n = 54, mean ± SD), respectively, acceptable for high-quality in vivo extracellular recordings 32 .…”
Section: Resultsmentioning
confidence: 99%
“…There has recently been debate as to what extent impedance reduction is useful to improve neural recordings 38,39 . In fact, in the case of intracellular recordings, raising the impedance from the standard 5 MΩ to several hundred MΩ still produced good intracellular measurements provided that one uses appropriate amplifying electronics 40 .…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Thus, many publications suggest that it is not necessary to prioritize low impedance once it is significantly below the input impedance of the amplifier. Neto et al (2018) 38 One often undervalued parameter is the cost and ease of manufacturing. Though many varieties of experimental electrode have been published in the last decade, relatively few designs have proliferated and become commonly used.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…We confirmed that the effect of substrate doping density on the electrical and optical characteristics of the fabricated LEDs is not as significant as the die-to-die variation in a wafer ( Supplementary Figure 1). The impedance magnitude and phase of the recording electrodes were measured as 1.15 ± 0.07 M and -68.33 ± 5.11 ° at 1 kHz (n = 54, mean ± SD), respectively, acceptable for high-quality in vivo extracellular recordings 30 .…”
Section: Fabrication and Characterization Of Ministar Led Optoelectrmentioning
confidence: 99%